Chapter Le signorie del Mezzogiorno aragonese attraverso i libri dei relevi - d'Arcangelo, Potito (Reti Medievali E-Book, 2021)
The essay provides an overview on fiefs and seigneurial powers in the Kingdom of Naples in the Aragonese era, on the base of findings and research issues drawn on the serie Relevi kept at the Archivio di Stato of Naples. It includes discussions on demographic development and settle- ment patterns, successions, government and productive structures, the territorial vocation, the process of "monumentalization" of the seigneurie in the medieval and early-modern southern sources.